INTERNALIZATION OF HAREFA LOCAL WISDOM VALUES IN GUIDANCE AND COUNSELING SERVICES TO DEVELOP STUDENTS’ INTEGRITY-BASED CHARACTER IN THE NIAS ISLANDS - Darmawan Harefa (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
This study aims to thoroughly examine the process of internalizing the local wisdom values of Harefa in guidance and counseling (G&C) services to develop students’ integrity-based character in the Nias Islands. The local wisdom of Harefa, or harehare, has a cultural meaning as a place to store guests’ belongings and a philosophical meaning as a symbol of trustworthiness, responsibility, and respect for others. Using a library research approach, this study analyzes various theoretical sources and previous relevant research related to character education based on local wisdom. The findings indicate that integrating local values into G&C services can strengthen the contextual development of students’ character, as these values are deeply rooted in the culture and social life of the Nias community. G&C services that adapt Harefa values through group guidance activities, value reflection, and cultural discussions have been shown to be effective in fostering honesty, responsibility, and respect among students. This study emphasizes that the internalization of Harefa values not only serves as a means of preserving local culture but also functions as a strategic approach to shaping students into individuals with integrity, cultural identity, and strong character. Therefore, the local wisdom of Nias has great potential to serve as the foundation for developing a G&C service model based on regional cultural values.